Dinâmica espaço-temporal em um fragmento de savana decídua espinhosa, semi-árido do Brasil - Menezes, Bruno Sousa de (2010)
In the savanna environments, the variation in the density of the trees, due to a greater availability of the humidity in the soil, results in a heterogeneous and highly dynamic landscape in time and space. So, they constitute ideal places for testing the patch dynamics model in metacommunities. Ecological communities can be seen as an endowed system of auto-control mechanism. Taking on the vegetable communities as systems, it implies in accepting that they obey the common rules which govern any types of system, either they are biological or not. This way, the vegetable communities must present three main premises: (1) presenting structural and functional characters, in other words, it is possible to distinguish the elements which are composed, describing its arrangement in time and space and identifying the alterations among them; (2) not being a disorganized collection of elements, but, on the other way round, the manner in which species cohabit is structured in the organized form in time and space and (3) being a building resulting from the acting of the temporary processes which maintain certain temporal stability. Based on these premises, it was analyzed the spatio-temporal dynamics of the structural parameters (density and biomass) of the community and present populations in a fragment of the conserved vegetation. The analyses were done on a permanent plot of 1 hectare, installed in the Serra das Almas Natural Reservation, Ceara, in two distinct times (2002 and 2008). It was verified that the number of species, the composition and the total density of the system were practically constant in the interval of analyzed time. Therefore, the size of the populations was little altered and the community’s structure maintained stable. In the face of this, the community presented welldefined standards of co-occurrence, with tendency of structure for species competition. Spatially, occurred differences among neighbor places (plots), where the composition of each one defined which of them presented greater or smaller dynamicity. The considerable increase of the total above-ground biomass, potentially resulting from the antropic regeneration, demonstrates that the community analyzed finds itself in an intermediary state of the regeneration phase. Based on the spatially registered heterogeneity, it is verified that the patch dynamics model can be tested in small scale for evaluating the vegetation dynamics and, consequently, inferring on the capacity of the system support to the anthropogenic effects and climatic disturbances.